PERAN SOSIOLOGI MILITER DALAM PERTAHANAN DAN KEAMANAN NEGARA - Kol. H. Yusuf (Yayasan Nusantara Hasana Berdikari, 2023)
Yusuf, the role of military sociology in the defense and security of the state. This study is the result of discussion of the role of military sociology in Indonesia on the defense and security of the region, resulting in the following: (1) At the beginning of the revolution, the Government of Indonesia did not form an official army. Elements of forming BKR, TKR, TRI to TNI were built with three main elements each having different backgrounds ie former members of KNIL, former members of PETA, and the army of the people. Elements that later became the forerunner to the establishment of the TNI (Indonesian National Army) which later developed into the Army, Navy, and Air Force. The TNI is headed by a TNI Commander, while each force has a Chief of Staff of the Armed Forces. (2) The role of military sociology in the defense and security of the state can not be kept away from the basic role of the TNI itself. According to the TNI Law Article 7 paragraph (1), the main task of the Indonesian National Army is to uphold the sovereignty of the state, to maintain the territorial integrity of the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution, and to protect the whole nation and the whole of Indonesia from the threat and disturbance to the nation and country. (3) One form of military sociology is the kowil (Regional Command), the existence of Koramil and Babinsa in the community, can close and prevent the existence of opportunities for the development of organizations that become a latent danger for the state of Indonesia. The monitoring of loose territory due to Kowil personnel limitation, will give the communists the opportunity to grow rapidly, as indications of emergence of hazards that threaten the defense and security of the country are visible.